Women Safeguard Wing Application - Kobalan, Thamarai Selvi; Bin Hamzah, Dr Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2022)
Mobile applications available in smart phone are beneficial in disaster responses. One of that is GPS technology, which can be used in tracking of rescuers by providing location and also can be used for communication. Women Safeguard Wing application will act like an emergency assistant to help people during the emergency situation. This application keeps people in touch with their closest by instantaneously sending a photo, GPS information and other information when they need them the most. One of the problem women panic when they get into unexpected emergency situations. They might forget to alert the situation to their guardian or family members. Furthermore, lack of feature to post alert message in social network if women not able to contact their guardian or family members. This feature help to post alert messages in social network such as Facebook also help people during their emergency times. Furthermore, there is no locate me and check in functions. During emergency situation, most of the applications only can use during emergency situation not to notify their contacts about the whereabouts. Therefore, Women Safeguard Wing application is proposed to solve this problem. The objective of this project is to design a mobile application for alerting, notifying and locating victim’s whereabouts. Then, this mobile application is proposed so that can it be used for a personal safety to protect on emergency situation. Moreover, Women Safeguard Wing application is also proposed to evaluate as a simple medium to create awareness. The methodology chosen for implement Women Safeguard Wing Application is System Development Life Cycle (SDLC). Waterfall model is chosen model to build this proposed system. The core function of this application is to inform peoples’ emergency situation to other and get help and also to keep in touch with their closed family members. When someone in an emergency situation, they can just press the emergency panic button interface of the application to activate the system to send emergency alert via SMS. The application will send an emergency message with pre-programmed text and current GPS location using Google map of the person through SMS, WhatsApp, Email and other resources according to the choice of the person to emergency contact which saved in the application. This proposed application is user friendly and easy to learn which let user to inform their whereabouts using this application. User should have stable internet connection to activate the trigger button which may help to track their GPS location using Google map on emergency situations.